Fundamentos das normas extrafiscais : a perspectiva jusnaturalista como alternativa às insuficiências do juspositivismo e do neoconstitucionalismo - Kronbauer, Eduardo Luís (2018)
This study aims to develop a reasoning of tax rules with simulative function under the point of view of the natural law, indicating the natural law theory perspective as the best alternative against to the other existent legal theories standpoint. First, the study presents, in a critical view, the philosophical preconditions of the two doctrines that predominate the actual paradigm: legal positivism and “neoconstitucionalism”. It demonstrates that these theories are in the opposite extremes and follow incommunicable ways, and both show insufficiencies in its justifications. Therefore, this present research sustains that the preconditions capable of revealing a more efficient and complete reasoning of the inducing tax rules can be find in the theory of natural law. Thereby, the justification presented in this paper stablishes the idea of natural law, basic goods, justice, finalities. Legitimacy and form of law as the elements capable of justify the taxation with simulative function.